2016
DOI: 10.15343/0104-7809.20164001106113
|View full text |Cite
|
Sign up to set email alerts
|

Riscos ocupacionais dos técnicos em radiologia na assistência ao portador de múltiplos traumas

Abstract: Este estudo objetivou identificar e dar visibilidade aos principais riscos ocupacionais de técnicos em radiologia, associados à assistência ao paciente portador de múltiplos traumas, em um serviço hospitalar de radiologia convencional. Pesquisa exploratório-descritiva com abordagem qualitativa. A coleta de dados ocorreu por meio da técnica de observação participante dos atendimentos efetuados pelos técnicos em radiologia num serviço de radiologia convencional de um hospital geral de Florianópolis entre maio e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Thus, according to the legislation recommended, continuing education, sustained by a periodic update, should be institutionalized, since it recognizes the possible risk to which professionals working in radiodiagnosis services are exposed. Moreover, in training for the development of practical skills, it could be included improvement projects for self-care with regard to workers' health (Anderson et al, 2016;Régis et al, 2018).…”
Section: Discussion:-mentioning
confidence: 99%
“…Thus, according to the legislation recommended, continuing education, sustained by a periodic update, should be institutionalized, since it recognizes the possible risk to which professionals working in radiodiagnosis services are exposed. Moreover, in training for the development of practical skills, it could be included improvement projects for self-care with regard to workers' health (Anderson et al, 2016;Régis et al, 2018).…”
Section: Discussion:-mentioning
confidence: 99%
“…Problems are also posed by broken gurneys, or with locks and wheels which do not work properly, insufficient numbers of workers available to transfer patients from gurneys to the x-ray table, and having to handle weights above the shoulder level while handling equipment or positioning patients. All these factors might result in overload to the joints and spine 7 .…”
Section: Discussionmentioning
confidence: 99%
“…A study performed by Anderson 6 found that beyond the common burdens associated to hospital work, this group is also exposed to factors inherent to the work process in radiology. Such risks include: exposure to ionizing radiation, large numbers of patients, working with broken equipment, exposure to body fluids, ergonomic risks related to handling weights, and accelerated pace of work 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these elements, we highlight ionizing radiation, presence of micro-organisms in body fluids and secretions, accelerated work pace, scarcity of human resources, and excessive weight manipulation. 2 …”
Section: Introductionmentioning
confidence: 99%